2023
DOI: 10.1155/2023/6726038
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Hub Genes Related to Osteoporosis Were Identified by Bioinformatics Analysis

Abstract: Osteoporosis (OP) is commonly encountered, which is a kind of systemic injury of bone mass and microstructure, leading to brittle fractures. With the aging of the population, this disease will pose a more serious impact on medical, social, and economic aspects, especially postmenopausal osteoporosis (PMOP). This study is aimed at figuring out potential therapeutic targets and new biomarkers in OP via bioinformatics tools. After differentially expressed gene (DEG) analysis, we successfully identified 97 upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…CCL7 belongs to the CC chemokine family and its role in osteoporosis is currently under study [ 64 ]. RANKL induces the expression of many chemokines including CCL7, to enhance osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%
“…CCL7 belongs to the CC chemokine family and its role in osteoporosis is currently under study [ 64 ]. RANKL induces the expression of many chemokines including CCL7, to enhance osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%
“…Another bioinformatics technique, xCell, can evaluate immune cell composition in diseases [ 21 ]. While some studies have identified hub genes associated with primary osteoporosis (PMOP) [ 22 , 23 ], few have combined WGCNA and Machine Learning to select hub genes and focus on immune infiltration levels and related biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%